2012
DOI: 10.1523/jneurosci.5705-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Retinal Neurodegeneration in a Model of Multiple Sclerosis

Abstract: Neurodegeneration plays a major role in multiple sclerosis (MS), in which it is thought to be the main determinant of permanent disability. However,therelationshipbetweentheimmuneresponseandtheonsetofneurodegenerationisstillamatterofdebate.Moreover,recentfindings in MS patients raised the question of whether primary neurodegenerative changes can occur in the retina independent of optic nerve inflammation. Using a rat model of MS that frequently leads to optic neuritis, we have investigated the interconnection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 48 publications
(53 reference statements)
9
57
1
Order By: Relevance
“…In the same animal model apoptosis of retinal ganglion cells with decline of visual function in electrophysiological recordings was observed in the preclinical phase of EAE. At this time point no histopathological abnormalities were detected in the optic nerve [12, 14]. In MOG-EAE model in mice axonal loss in the spinal cord was detected before clinical manifestation of the disease [15].…”
Section: Discussionmentioning
confidence: 99%
“…In the same animal model apoptosis of retinal ganglion cells with decline of visual function in electrophysiological recordings was observed in the preclinical phase of EAE. At this time point no histopathological abnormalities were detected in the optic nerve [12, 14]. In MOG-EAE model in mice axonal loss in the spinal cord was detected before clinical manifestation of the disease [15].…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that RGC somas atrophy before the axons even though in retrograde degeneration, axonal pathology/dysfunction precedes that of ganglion cell body. Fairless et al 25 demonstrated in a rat model of MS, that at the time of significant RGC soma loss, the axons appeared to be intact in numbers but showed ultrastructural signs of degeneration. Recent studies in glaucoma demonstrated the value of measuring macular RGC.…”
Section: Discussionmentioning
confidence: 99%
“…Bielschowsky’s silver impregnation was performed in order to depict axonal pathology, as previously described55. To further assess axonal degeneration, immunohistochemistry was performed using an antibody against APP as described previously57.…”
Section: Methodsmentioning
confidence: 99%